Formation and stability of gold nanoparticles in colloids prepared by citrate method - N. V. Vityuk; A. M. Eremenko; N. M. Rusinchuk; V. Z. Lozovski; M. M. Lokshyn; V. S. Lysenko; Iu. P. Mukha (Хімія, фізика та технологія поверхні)
Gold nanoparticles (Au NPs) have found a variety of applications in different areas, particularly in biomedical practices. The activity of Au NPs strongly depends on the size and association of particles in colloid, that in turn are greatly affected by experimental parameters of the reaction. The obtaining of Au NPs even via classical procedure of citrate method can be a challenge.